Usulan Metode KPI Transmisi Tenaga Listrik pada Perusahaan Listrik Negara (PT. PLN) Berdasarkan Balanced Scorecard - Putera, Hilmana Radhia; Fernando, Very (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
PT. Perusahaan Listrik Negara (PLN) is an Indonesian electricity provider. In the midst of rapid global changes, PLN is required to always be ahead in terms of service quality, sustainable business models, and technological developments. PLN must always be ahead in terms of service quality, sustainable business models, and technological developments. To support PT. PLN, appropriate performance measurements, such as those for electricity transmission performance, are required. Electricity transmission performance can be measured using Key Performance Indicators (KPIs). PT. PLN's KPIs in 2019 show that two performance indicators, SAIDI and SAIFI, did not reach their targets. Additionally, the company's sustainability report only contains two performance indicators, but performance measurement could be expanded to include other indicators. This research aims to identify the appropriate performance indicators for PT. PLN's electricity transmission system and to establish strategic goals for the company. PLN using the balanced scorecard method. Based on a literature review and analysis, this study identified the following performance indicators: SAIFI, SAIDI, CAIDI, AIT, OHLMCI, SMCIS, and the ratio of certified officers. Five strategic objectives were obtained, including increased ROA and ROI, increased customer satisfaction, increased opportunities for uninterrupted energy sales, increased equipment reliability, and increased employee competency in inspection and maintenance.